Understanding the persistence of hexachlorobenzene and its intermediates in agricultural chemical usage areas - Sudjarid, Wichidtra; Jarupunphol, Pita (Creative Science, 2024)
This study examined the presence and distribution of Hexachlorobenzene (HCB) and its derivatives in sediment samples. The investigation was conducted in a watershed along the Lum Stream agricultural area during the 2021 rainy season. The results showed HCB persistence despite being banned for a prolonged period. The water quality, indicated by the suspended solids (SS) and organic content, was evaluated at ten different observation points. However, only trace amounts of chemicals were detected in the sediment samples. The concentration levels of HCB, PeCB, and 1235-TeCB in the sediments ranged from 0.032 to 0.631 ppm, 0.018 to 0.485 ppm, and 0.091 to 0.366 ppm, respectively. The relationship between HCB, SS, and organic content was analyzed monthly, revealing interesting patterns. For instance, June and July exhibited similar trends, while HCB and its intermediates were negatively correlated with distance in September. Furthermore, a positive correlation was observed between 1235-PeCB and BOD of 0.48. This implies that as the amount of 1235-PeCB increased in the sediment samples, the BOD of the water also increased, suggesting a possible impact of 1235-PeCB on the water quality. GRAPHICAL ABSTRACT HIGHLIGHTS Persistent Organic Pollutants (POPs) have been detected in trace amounts over an extended period, constituting a part of the environmental compartment where they remain. The re-emergence of suspended solids in river water is likely to have a significant correlation with the concentration of Hexachlorobenzene (HCB) and its intermediary compounds.